Beispiel Nr: 11
$ \text{Gegeben:}\\ \text{Kathete} \qquad a \qquad [m] \\ \text{Kathete} \qquad b \qquad [m] \\ \\ \text{Gesucht:} \\\text{Hypotenuse} \qquad c \qquad [m] \\ \\ c =\sqrt{a^{2} + b^{2} }\\ \textbf{Gegeben:} \\ a=\frac{1}{3}m \qquad b=1m \qquad \\ \\ \textbf{Rechnung:} \\ c =\sqrt{a^{2} + b^{2} } \\ a=\frac{1}{3}m\\ b=1m\\ c =\sqrt{(\frac{1}{3}m)^{2} + (1m)^{2} }\\\\c=1,05m \\ \small \begin{array}{|l|} \hline a=\\ \hline 0,333 m \\ \hline 3,33 dm \\ \hline 33,3 cm \\ \hline 333 mm \\ \hline 3,33\cdot 10^{5} \mu m \\ \hline 0,000333 km \\ \hline \end{array}\\ \small \begin{array}{|l|} \hline b=\\ \hline 1 m \\ \hline 10 dm \\ \hline 100 cm \\ \hline 10^{3} mm \\ \hline 10^{6} \mu m \\ \hline 0,001 km \\ \hline \end{array}\\ \small \begin{array}{|l|} \hline c=\\ \hline 1,05 m \\ \hline 10,5 dm \\ \hline 105 cm \\ \hline 1,05\cdot 10^{3} mm \\ \hline 1,05\cdot 10^{6} \mu m \\ \hline 0,00105 km \\ \hline \end{array}\\$